UJI BEBERAPA JENIS DAN DOSIS CENDAWAN MIKORIZA ARBUSKULA SERTA ADOPSI METODA SRI ( The System of Rice Intensification) TERHADAP PERTUMBUHAN DAN PRODUKSI PADI GOGO PADA ULTISOL - Yusnaweti Yusnaweti; Sevindrajuta Sevindrajuta (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2009)
An experiment about “Effects of Arbuscular Mychorhizae Fungi and Adoption of SRI Method on the Growth and Production of Upland Rice on Ultisol” was conducted in glasshouse and soil laboratory of Agriculture Faculty, University of Andalas, Padang. The objective was to obtain the best species and optimum rate of Arbuscular Mycorrhizaze Fungi (AMF) for increasing growth and productivity of upland rice in Ultisol. This was designed in a Factorial Experiment which was allocated in Completely Randomized Design, with two factors and four replications. The first factor was species of AMF (Glomus manihotis, Glomus fasiculatum, and Gigaspora rosea), and the second factor was the application rate of the AMF (0, 5, and 10 g/pot). Variety of upland rice being used was Danau Gaung. The results of the experiment indicated that AMF from species Glomus fasiculatum with 5 g/pot or planting hole showed the best growth and highest production of upland rice in Ultisol.Key words: Arbuscular Mycorrhizae Fungi (AMF), upland rice, Ultisol